2013
DOI: 10.1074/jbc.m112.390146
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state NMR Study Reveals Collagen I Structural Modifications of Amino Acid Side Chains upon Fibrillogenesis

Abstract: Background: Collagen fibrillogenesis is a fundamental process both in vivo and in vitro. Results: Fibrillogenesis increases the heterogeneity of conformations of side chain amino acids, impacting 40% of imino acids. Conclusion: A temperature-induced-attractive force component comes from significant amount of the collagen amino acids. Significance: This work brings new perspectives to studies of collagen assembly and interactions with other matrix molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 36 publications
(94 reference statements)
1
28
0
Order By: Relevance
“…Therefore, the difference between NOE and quantitative spectra provide information on the relative mobility of the protein structures. Assignment and simulation of the peaks to structures was achieved as in Peixoto et al 45 Spectra exhibited well-resolved peaks with narrow line width for many carbons, suggesting that parts of the assembled SlpA were highly mobile ( Figure 4). This thinness of the peaks can be explained either by fast dynamics and/or by the fact that many carbons displayed exactly the same chemical shift.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, the difference between NOE and quantitative spectra provide information on the relative mobility of the protein structures. Assignment and simulation of the peaks to structures was achieved as in Peixoto et al 45 Spectra exhibited well-resolved peaks with narrow line width for many carbons, suggesting that parts of the assembled SlpA were highly mobile ( Figure 4). This thinness of the peaks can be explained either by fast dynamics and/or by the fact that many carbons displayed exactly the same chemical shift.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thus rapid Pro ring flips between endo and exo conformations results in an isotropic 13 C signal at the population-weighted average chemical shift between those for the endo and exo conformations. In their study, De Sa Peixoto and collaborators [16] showed that upon fibrillogenesis, the proline C and C undergo increases in their respective 13 C chemical shifts by up to 0.6 ppm, suggesting a Pro ring conformational preference more towards the exo conformation for collagen molecules in fibrils compared to those in solution. Conversely, the hydroxyproline, 13 C chemical shift does not change much upon fibril formation.…”
Section: Collagen Molecular Dynamicsmentioning
confidence: 98%
“…De Sa Peixoto and co-workers [16] have investigated the changes in collagen molecular conformation associated with the formation of collagen nanofibrils through observing changes in 13 C chemical shift in key collagen amino acid residues between soluble collagen at acidic pH, fibrillar collagen in dense, pure collagen matrices, and denatured collagen, the latter being a reference for 13 C chemical shifts of collagen in a random coil conformation. They used natural abundance 13 C (unlabelled) collagen and 2D 1 H- 13 C correlation spectra to improve 13 C spectral resolution over that in 1D 13 C NMR spectra.…”
Section: Collagen Molecular Structure By Nmrmentioning
confidence: 99%
See 1 more Smart Citation
“…Packing of the collagen fibrils relies on changes in amino acid conformation along the chain. 56 A macroscopic effect of the change in structure is readily seen in the different assembly rates of collagen types. Collagen type III and II form fibrils faster than type I, due to higher molecular mass of type I and fewer intermolecular interactions.…”
Section: Building a Network: Collagen Fibrillogenesismentioning
confidence: 99%